APLIKASI RESEP MASAKAN BERBASIS ANDROID - Christina, Sherly; Ronaldo, Deddy; Zaini, Rosya Marullah (STMIK Palangkaraya, 2021)
Cooking Recipe is a culinary element that often attracts culinary lovers. A cooking recipe is a guidance for preparing the ingredients, how to cook and serve the dish. The collection of recipes which documented in the printing media have not been able to meet the needs of culinary lovers with high mobility. This study aims to develop an Android-based recipe application to meet the culinary lovers need of a technology for storing recipes collection that can be accessed easily. We apply the Luther multimedia development method, which consists of the concept, design, material collecting, assembly and testing phases. The Android platform will provide the recipe application features, and the website platform will provide the content management features for managing the contents in the recipe application. The result of black box testing on the application shows that the features in the recipe application perform according to the expected concept and design. For the future research, to improve the application performance, we will build social media features for the members and a data mining system for processing big data from the recipe collection to produce valuable information.